2023
DOI: 10.1186/s12964-023-01107-2
|View full text |Cite
|
Sign up to set email alerts
|

Snail mediates GDF-8-stimulated human extravillous trophoblast cell invasion by upregulating MMP2 expression

Abstract: Background Extravillous trophoblast (EVT) cell invasion is a tightly regulated process that requires for a normal pregnancy. The epithelial-mesenchymal transition (EMT) has been implicated in EVT cell invasion. Growth differentiation factor-8 (GDF-8), a member of the transforming growth factor-beta (TGF-β) superfamily, is expressed in the human placenta and promotes EVT cell invasion by upregulating the expression of matrix metalloproteinase 2 (MMP2). However, the underlying molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…MSTN has previously been shown to induce the phosphorylation of receptor regulated SMAD2/3 in human trophoblast cells. [23][24][25][26] Moreover, we 23 and others 24 have shown that the invasive effects of MSTN on human trophoblast cells are mediated by ALK5 and not ALK4. Previous studies have characterized cell-type specific differential involvement of ALK4/5 in MSTN-dependent roles; MSTN preferentially binds to ALK4 in myoblast cells as opposed to binding ALK5 in nonmyogenic tissues.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…MSTN has previously been shown to induce the phosphorylation of receptor regulated SMAD2/3 in human trophoblast cells. [23][24][25][26] Moreover, we 23 and others 24 have shown that the invasive effects of MSTN on human trophoblast cells are mediated by ALK5 and not ALK4. Previous studies have characterized cell-type specific differential involvement of ALK4/5 in MSTN-dependent roles; MSTN preferentially binds to ALK4 in myoblast cells as opposed to binding ALK5 in nonmyogenic tissues.…”
Section: Discussionmentioning
confidence: 75%
“…This is likely related to technical and interpatient variability as well as the small sample size and duration of MSTN treatment (i.e., single time-point). For example, the rapid induction (3-6 h) of Snail and Slug mRNA by MSTN reported by Chen et al might explain why these EMT transcription factors did not appear as DEGs in our analysis at 24 h. 26 A major contributor to interpatient variability is the inability to predict pregnancy outcome of the first trimester samples used for trophoblast isolation, which could yield a mix of normal and diseased placentas. 27 Indeed, we did not have access to any of the associated clinical data (e.g., maternal age, parity, reason for pregnancy termination, history of placenta-mediated diseases) for the samples used in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, it has been demonstrated that activating this signaling pathway stimulates the expression of MMP2 , thereby mediating the upregulation of invasive capabilities in human extra villous trophoblast cells ( Fang et al, 2021 ). Moreover, it facilitates trophoblast mobility, regulates invasion, and promotes the expression of FSTL3, thereby influencing invasive capabilities ( Xie et al, 2020 ; Fang et al, 2021 ; Chen et al, 2023 ). According to previous studies, GDF-8 binds to the receptor ALK5, activating the SMAD2/3 complex.…”
Section: Discussionmentioning
confidence: 99%